Projecting history: a socio-semiotic approach to the representations of the military dictatorship (1976-1983) in the cinematic discourses of Argentine democracy - Triquell, Ximena (2000)
This thesis analyzes a series of films that, in different ways, seek to represent the last Argentine dictatorship. The possibility of interpreting the thematic and formal recurrences of the films as a defining characteristic of a specific genre is posed as a first hypothesis. The second hypothesis postulates the possibility of relating certain aesthetic and rhetorical changes of the series to certain socio-political processes.